SOSIALISASI DAN PELATIHAN PEMBUATAN VIRGIN COCONUT OIL BAGI MASYARAKAT DESA PARIT BANJAR - Fitriani Fitriani; Fahrur Rozi; Rinaldy Maundry; Sekar Indah Sari; Imanda Kharisna; Muhammad Fadhilah; Kanti Rahayu; Nurul Bait Atthoharoh; Melanie Melanie; Nanda Cahaya Imanniar (Jurnal Pengabdian Masyarakat, 2025)
The socialization and training of Virgin Coconut Oil (VCO) production were carried out by the community service team together with the women’s group (PKK) in Parit Banjar Village. This activity aimed to improve knowledge, skills, and the utilization of local coconut resources into products of economic value. The team delivered material on the benefits of VCO, its production process, and potential business opportunities. Participants took part in hands-on practice using a simple fermentation method with fresh coconuts as the raw material. During the practice, participants learned the stages of grating, squeezing coconut milk, fermenting, and separating pure oil. The results showed that participants were actively engaged in discussions. This activity provided an understanding that VCO production does not require complicated technology and can be carried out independently at home. Therefore, the socialization and practice of VCO production enhanced the skills of PKK members while also creating opportunities for small-scale entrepreneurship based on local resources.